Effectiveness of the Implementation of Social Rehabilitation for Child Victims of Sexual Violence Based on Justice (Case Study of UPTD PPA (Protection of Women and Children) of Kotamobagu City) - Malau, Nike Rumondang; Laksana, Andri Winjaya (Jurnal Hukum Khaira Ummah, 2025)
Children are a gift from God Almighty who have the right to be given protection for their personality and the rights inherent in a child. , therefore we must always protect children because in them inherent dignity, honor, and rights as human beings must be upheld. Children's human rights are part of human rights contained in the 1945 Constitution and the United Nations Convention on the Rights of the Child. From the perspective of national and state life, children are the future of the nation and the next generation of the nation's ideals, so that every child has the right to survival, growth and development and the right to protection from violence and discrimination as mandated in Article 28 paragraph (2) of the 1945 Constitution. Based on the formulation of the problem and the objectives of this research, the type of research used in this thesis research is empirical legal research, namely research that not only examines normative aspects but also examines how the law is implemented in society. Based on the Author's research by conducting interviews with the Head of UPTD PPA Kotamobagu City (Susilawati Gilalom), Psychologist Assistant (Indri Dilapanga) and Social Worker (Supriono Paputungan) regarding the implementation of social rehabilitation of child victims of sexual violence at the PPA Office of Kotamobagu City from the results of the interview, the Author can conclude that the implementation of the social rehabilitation process for child victims of sexual violence has been carried out well following the mechanisms and procedures regulated in the Regulation of the Minister of State for the Empowerment of Women and Child Protection of the Republic of Indonesia Number 2 of 2011 concerning Guidelines for Handling Child Victims of Sexual Violence, there are several obstacles found in the implementation of social rehabilitation of child victims of sexual violence